Early prediction of disease progression in COVID-19 pneumonia patients with chest CT and clinical characteristics - Zhichao Feng (Nature Portfolio, 2020)
Early identification of COVID-19 patients at risk of progression may facilitate more individually aligned treatment plans. Here the authors develop an online nomogram incorporating CT severity score and clinical characteristics for early predicting the disease progression risk among COVID-19 pneumonia patients.